Pengembangan Aplikasi E-Commerce Untuk Pemesanan Biji dan Bubuk Kopi Berbasis Android - Subhi, M Ramadhan; Nurfebruary, Nanda Sitti; Fhonna, Rizky Putra (Journal of Information System Research (JOSH), 2025)
The rapid advancement of information technology has driven digital transformation across various sectors, including product marketing. Deputroe Coffee, a local business that sells Gayo coffee beans and ground coffee, still relies on conventional sales methods that limit market reach and distribution efficiency. This research aims to design and develop an Android-based e-commerce application to facilitate the online ordering and selling of coffee products. The system development follows the waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The application features include user registration, product ordering, shopping cart management, and payment confirmation. Testing results indicate that the application functions as expected and is well-received by users. The implementation of this system has proven effective in improving marketing efficiency, expanding customer reach, and supporting the digital transformation of micro-enterprises in the coffee sector. This research is expected to serve as an effective solution to enhance the competitiveness of Deputroe Coffee through the use of information technology.